MANAJEMEN ASET DAERAH KOTA PEKANBARU (STUDI KASUS MOBIL DINAS) - Limbong, Nike Ima Elia; Yuliani, Febri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Asset manajemen of Pekanbaru area case study official car current public concern which has not been maximal asset management area viewed by phenomenas that exist, there few device work unit area not finished yet to trace his official car, the Audit Board of the Republic of Indonesia on financial management and asset Pekanbaru area within the last seven years get opinion qualified opinion six time in a row, still there former member of the official car Member of Parliament Pekanbaru is be returned yet, there is still the official car used to shopping areas or not on purpose. Formulation of the problem in this research is how asset management of Pekanbaru Area (case study official car) and what factors affect the asset management of Pekanbaru Area (case study official car).The purpose of this research is to understand and analyze asset management of Pekanbaru Area (case study official car) and factors affect the asset management of Pekanbaru Area (case study official car). This research uses Siregar theory eith indicator: asset inventory, legal audit, asset valuation, asset optimization, and supervision and controlling.This research methods is using exploratory qualitative approach. Informants in this research are member or Financial Management Agency Pekanbaru City Asset, the Area Secretariat, civil service police unit, Member of Parliament Pekanbaru, user official car, Data collection techniques in this research are interviews, observation and documentation.The results of this research is the performance of asset management of Pekanbaru Area less than maximal. This was evidenced by there few device work unit area not finished yet to trace his official car, the Audit Board of the Republic of Indonesia on financial management and asset Pekanbaru area within the last seven years get opinion qualified opinion six time in a row, still there former member of the official car Member of Parliament Pekanbaru is be returned yet, there is still the official car used to shopping areas or not on purpose. Factors affecting the performance of the immigration office of human resources, tasks, policiesKeywords: Asset Management and Official Car